2014
DOI: 10.1111/jcmm.12361
|View full text |Cite
|
Sign up to set email alerts
|

Elongation factor‐2 kinase regulates TG2/β1 integrin/Src/uPAR pathway and epithelial–mesenchymal transition mediating pancreatic cancer cells invasion

Abstract: Pancreatic ductal adenocarcinoma is one of the lethal cancers with extensive local tumour invasion, metastasis, early systemic dissemination and poorest prognosis. Thus, understanding the mechanisms regulating invasion/metastasis and epithelial–mesenchymal transition (EMT), is the key for developing effective therapeutic strategies for pancreatic cancer (PaCa). Eukaryotic elongation factor-2 kinase (eEF-2K) is an atypical kinase that we found to be highly up-regulated in PaCa cells. However, its role in PaCa i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 85 publications
0
56
0
1
Order By: Relevance
“…Eukaryotic elongation factor‐2 kinase (eEF‐2K), an atypical kinase, is increased in pancreatic cancer cells. Recent studies show that suppression of eEF‐2K with siRNA impairs pancreatic cancer cell migration/invasion and that this is associated with reduced TG2 level and reduced EMT . Thus, as described for other cancer cell types, loss of TG2 is associated with reduced EMT .…”
Section: Tg2 Role In Various Cancer Typesmentioning
confidence: 82%
“…Eukaryotic elongation factor‐2 kinase (eEF‐2K), an atypical kinase, is increased in pancreatic cancer cells. Recent studies show that suppression of eEF‐2K with siRNA impairs pancreatic cancer cell migration/invasion and that this is associated with reduced TG2 level and reduced EMT . Thus, as described for other cancer cell types, loss of TG2 is associated with reduced EMT .…”
Section: Tg2 Role In Various Cancer Typesmentioning
confidence: 82%
“…Moreover, knockdown of eEF2K reduces cell invasion and migration, and reduces TG2 mRNA and protein level. TG2 appears to have a role in regulating downstream signaling events, as knockdown of either eEF2K, or TG2, reduces Snail and ZEB1 level leading to reduced EMT (Figure A) Thus, eukaryotic elongation factor‐2 kinase appears to utilize TG2 to enhance pancreatic cancer cell migration, invasion and EMT. TG2 also regulates pancreatic cell morphology, since TG2 silencing reduces the 2‐O‐tetradecanoylphorbol‐13‐acetate dependent phosphorylation of keratin 8, and suppresses 2‐O‐tetradecanoylphorbol‐13‐acetate dependent keratin filament reorganization in PANC‐1 cells .…”
Section: Tg2 In Tumor Typesmentioning
confidence: 98%
“…Eukaryotic elongation factor‐2 kinase (eEF2K) is a negative regulator of protein elongation that acts via phosphorylation of eukaryotic elongation factor 2 (eEF2), and is a key component of the translation machinery . eEF2K is overexpressed in pancreatic cancer cells and is associated with elevated TG2 level (Figure A). Moreover, knockdown of eEF2K reduces cell invasion and migration, and reduces TG2 mRNA and protein level.…”
Section: Tg2 In Tumor Typesmentioning
confidence: 99%
“…However, this metastasis induced by β1 integrin depends on the expression of EGFR and the phosphorylation of AKT, which is a downstream signaling protein of EGFR (20). Furthermore, in certain types of cancer, the data demonstrated that β1 integrin may activate Src or phosphorylate p38 and AKT to affect urokinase-type plasminogen activator (uPA), and matrix metalloprotease (MMP)-2, promoting the metastasis of cancer cells (21,22). Additionally, due to the lack of vasculature, cancer cells enhance β1 integrin activity to induce vessel cooption by adhering to the vascular basement membrane, thus providing immediate vasculature structures for newly metastatic or locally invasive of cancer cells (23).…”
Section: Metastasismentioning
confidence: 99%